2016
DOI: 10.1071/sr15273
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the cotton irrigation network to farm nitrous oxide emissions

Abstract: Nitrous oxide (N2O) is a potent greenhouse gas, and agriculture is the dominant source of N2O-N emissions. The Australian cotton industry requires high inputs of N to maintain high lint quality and yields; however, over-fertilisation with N is symptomatic of the industry. Up to 3.5% of N fertiliser applied is lost directly from cotton fields as N2O gas. Excess N may also be lost via erosion, deep-drainage, leaching and runoff, and may subsequently form indirect N2O emissions. The estimate by the Intergovernmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This corresponds to about 3% of all N 2 O emissions and about one third of IPCC's previous estimate of 1.7 Tg N year −1 in the 4th Assessment Report for the same systems. Several studies have highlighted that emissions from rivers might be underestimated (Beaulieu et al, 2011) or significantly overestimated (Hu, Chen, & Dahlgren, 2016;Macdonald, Nadelko, Chang, Glover, & Warneke, 2016) in the IPCC assessments (Table 1). A recent review of estuarine emissions (Murray, Erler, & Eyre, 2015) also suggested that these aquatic systems could emit about three times more N 2 O (0.31 Tg N year −1 ) than the latest IPCC estimate.…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds to about 3% of all N 2 O emissions and about one third of IPCC's previous estimate of 1.7 Tg N year −1 in the 4th Assessment Report for the same systems. Several studies have highlighted that emissions from rivers might be underestimated (Beaulieu et al, 2011) or significantly overestimated (Hu, Chen, & Dahlgren, 2016;Macdonald, Nadelko, Chang, Glover, & Warneke, 2016) in the IPCC assessments (Table 1). A recent review of estuarine emissions (Murray, Erler, & Eyre, 2015) also suggested that these aquatic systems could emit about three times more N 2 O (0.31 Tg N year −1 ) than the latest IPCC estimate.…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying indirect N 2 O emissions from leaching and runoff requires measurement of NO 3 − –N and N 2 O concentrations in groundwater, surface drainage, rivers, and estuaries, but not direct measurement from transported sediments. Macdonald, Nadelko, Chang, Glover, and Warneke () demonstrated the relatively small scale of indirect N 2 O emissions from furrow‐irrigated cotton paddocks through analysis of water from irrigation channels and storage areas but conceded that further indirect N 2 O emissions (from sediments) would occur as the irrigation furrows, tail drains, and channels dried down (not measured). Fertilized upslope soils that remain uncropped are not specifically included as a source of indirect emissions, but perhaps should be.…”
Section: Discussionmentioning
confidence: 99%
“…4 and 5 indicated that excess N is being applied to the fields in response to a lack of lint production. Unfortunately, the majority of this N is lost via denitrification to the atmosphere, with a portion also lost in surface run-off, transformed and lost as the powerful greenhouse gas nitrous oxide (N 2 O), or lost to deep drainage, potentially affecting groundwater systems (Macdonald et al 2016b). These losses further emphasise the importance of improving NFUE across the industry.…”
Section: Field Trial Datamentioning
confidence: 99%
“…Recirculation of tail-water is the practice of Australian cotton industry, with moderate concentrations of residual N in supply channels leached from the hills in the fields (Macdonald et al 2016b). As such, N losses can occur from the irrigation network external to the field regardless of whether intentional fertigation is occurring.…”
Section: Improving N Translocation Within Cotton Plantsmentioning
confidence: 99%